Characterization of Specific Ion Effects on PI(4,5)P(2) Clustering: Molecular Dynamics Simulations and Graph-Theoretic Analysis - Han, Kyungreem (J Phys Chem B, 2020)
Numerous cellular functions mediated by PI(4,5)P(2) (PIP(2)) involve clustering of the lipid as well as co-localization with other lipids. Although the cation-mediated electrostatic interaction is regarded as the primary clustering mechanism, the ion-specific nature of the intermolecular network formation makes it challenging to characterize the clusters. Here we use all-atom molecular dynamics (MD) simulations of PIP(2) monolayers and graph-theoretic analysis to gain insight into the phenomenon. MD simulations reveal that the intermolecular interactions preferentially occur between specific cations and phosphate groups (P1, P4, and P5) of the inositol headgroup with better-matched kosmotropic/chaotropic characters consistent with the law of matching water affinities (LMWA). Ca(2+) is strongly attracted to P4/P5, while K(+) preferentially binds to P1; Na(+) interacts with both P4/P5 and P1. These specific interactions lead to the characteristic clustering patterns. Specificially, the size distributions and structures of PIP(2) clusters generated by kosmotropic cations Ca(2+) and Na(+) are bimodal, with a combination of small and large clusters, while there is little clustering in the presence of only chaotropic K(+); the largest clusters are obtained in systems with all three cations. The small-world network (a model with both local and long-range connections) best characterizes the clusters, followed by the random and the scale-free networks. More generally, the present results interpreted within the LMWA are consistent with the relative eukaryotic intracellular concentrations Ca(2+) << Na(+) < Mg(2+) < K(+); i.e., concentrations of Ca(2+) and Na(+) must be low to prevent damaging aggregation of lipids, DNA, RNA and phosphate containing proteins.